Kesadaran Pelajar Bahwa Dirinya Adalah Pelaku Pelecehan Seksual Verbal Di Dunia Pendidikan - Ariani Galuh Pangastuti; Noerma Kurnia Fajarwati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research is motivated by observational data showing "Student Awareness That They Are Perpetrators of Verbal Sexual Harassment in the World of Education" to respond to this, the researchers conducted research at Senior High School (SMA) which aims to find out students' far-reaching responses about (1) an increase in verbal sexual? (2) Angry away knowledge of forms of verbal sexual hatred? (3) Who is the perpetrator of verbal abuse that is most often found in the world of education? This research was conducted at a high school with a total of 65 respondents. This research measured all areas that the researcher wanted to know, namely: Analysis of the Average Verbal Sexual Harassment Ever Made by Respondents; Analysis of Respondents' Average Awareness Regarding Indecent Comments; Intimidating and seducing questions or interrogations about personal life; Whistling To Strangers; As well as Telling Dirty or Dirty Jokes to Someone is a Form of Verbal Sexual Harassment; Analysis of Respondents' Awareness That Men Can Also Become Victims of Verbal Sexual Harassment; Analysis of Average People Contacted When Experiencing Acts of Verbal Sexual Harassment; Average Analysis of Whether Respondents Have Had Discussions With Peers Or Have Ever Searched for Information Regarding Verbal Sexual Harassment Independently; Analysis of the Average Actions and Resistance Respondents Take If They or Their Friends are Perpetrators of Verbal Sexual Harassment